Black Women Coaches in Community: Promising Practices for Mentorship in Canada - Joseph, Janelle; McKenzie, Alex I. (Frontiers in Sports and Active Living, 2022)
Mentorship programs have been shown to help under-represented women navigate their environments, but little research has been done on mentorship programs in sport coaching in Canada. The first of its kind in Canada, the Black Female Coach Mentorship Program (BFCMP) created by the Black Canadian Coaches Association in partnership with the Coaching Association of Canada caters to an historically excluded population: Black, Biracial, and Indigenous women coaches. The research aimed to understand the experiences of program participants to better inform policy, decision-making, and sustainability of the BFCMP. Through mentorship session observations, one-on-one semi-structured interviews with 15 of the 27 inaugural BFCMP mentors and mentees, and thematic analysis, we determined the ability to form a trusted community was a promising practice for coach mentorship programs. Our findings suggest that participants, the majority of whom were the only Black woman coach in their program/institution, benefit from mentorship because of the opportunities to help each other develop as leaders, build relationships to resist loneliness, and nurture resilience through community.